On approximation of functions from below by splines of the best approximation with free nodes - Shumeiko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
Let M be the set of functions integrable to the power β=(r+1+1/p)-1. We obtain asymptotically exact lower bounds for the approximation of individual functions from the set M by splines of the best approximation of degree rand defect k in the metric of L p.